Tumor-infiltrating lymphocytes mediate complete and durable remission in a patient with NY-ESO-1 expressing prostate cancer - Elke Jäger; Julia Karbach; Claudia Wahle; Dragan Kiselicki; Kathrin Brand; Evgueni Sinelnikov; Dirk Gustavus; Hans Hoffmeister; Hans-Bernd Prisack; Akin Atmaca (Journal for ImmunoTherapy of Cancer)
Adoptive transfer of autologous tumor-specific lymphocytes represents a viable treatment method for patients with advanced malignancies. Here, we report a patient’s case with metastatic hormone-refractory New York esophageal squamous cell carcinoma 1 (NY-ESO-1) expressing prostate cancer treated with in vitro expanded tumor-infiltrating lymphocytes (TILs) in conjunction with IL-2 and immune-checkpoint blockade. Complete and durable tumor remission was observed after three TIL infusions consisting of 1.4×109, 2.0×109, and 8.0×109 T cells, respectively, lasting now for more than 3.5 years. Immunological correlates to the clinical development were the decrease of tumor-driven NY-ESO-1 serum antibody and the drop of prostate-specific antigen to <0.01 µg/L. TILs were reactive against cancer-testis antigen NY-ESO-1, individual tumor mutational proteins (eg, PRPF8, TRPS1), and the androgen receptor splice variant 12.